OpenFING: A Project based on a Digital Library of Recorded Courses. Issue 1 (14th December 2018) - Barreiro, Diego; Barzilai, Leticia; Canuti, Luciana; Carpani, Fernando; Del Arco, Lucía; Luna, Carlos; Raimondi, Clara
The OpenFING Project is an initiative by students for students, based on the creation and use of a digital video library of higher education courses, where students record video from standard lectures. The project attempts to address issues such as overcrowded lecture halls and students who work full time and thus cannot attend normal lectures. Today OpenFING seeks its consolidation along with an undergraduate introductory course on audiovisual and multimedia production. The project must be considered as a basis on which professors and students can develop teaching and learning innovations respectively, including different computer tools to support teaching and learning. In this article we describe the current status of OpenFING, six years after its creation; we describe the first study of how students and teachers perceive the initiative; and we conclude suggesting further developments.